IMPLEMENTASI METODE SCRUM DALAM PENGEMBANGAN WEBSITE E-COMMERCE PADA TWINS PETSHOP - Ayurira, Caren Legisna Aqila; Nur Fajri, Ika (Journal of Innovation And Future Technology (IFTECH), 2024)
Rapid technological advancements have triggered a significant global transformation in the digital economy. The utilization of digital technology has reshaped paradigms and behaviors across various aspects of life, including the business realm. Twins Petshop, as a mid-tier business player, faces several operational challenges, such as slow sales processes and limited promotional capabilities. To address these hurdles, the effective solution of developing an e-commerce website was pursued. This research implements the Scrum methodology in website development for Twins Petshop. Scrum methodology comprises five stages: product backlog, Sprint Planning, Daily Scrum, Sprint Review, and Sprint Retrospective. This approach was chosen for its superior flexibility and responsiveness to change, while also fostering intensive and productive team collaboration. Blackbox testing successfully identified and rectified functional errors, although further improvements are needed to bolster security aspects and enhance website functionality.